(untitled) (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the extent to which Law Number 20 of 2025 on the Criminal Procedure Code strengthens due process guarantees in Indonesia, particularly in relation to arrest, detention, and surveillance. The issue is legally significant because the new code introduces more explicit procedural safeguards, tighter coordination requirements between investigators and prosecutors, and broader pretrial review, but still leaves surveillance to be further governed by a separate statute. Using normative legal research with statutory, case, and conceptual approaches, this article compares the structure of Law Number 20 of 2025 with Law Number 8 of 1981, reads the reform in light of key Constitutional Court decisions, and formulates criteria for assessing whether coercive measures remain compatible with the rule of law. The article argues that the 2025 reform improves legal certainty for arrest and detention through clearer evidentiary thresholds, notification duties, time limits, and remedial consequences, yet the legality of surveillance will remain vulnerable unless an integrated supervisory regime is enacted and aligned with pretrial review.